The philosophy teacher: limits and possibilities - dynamics and problematization of teaching-learning (Educação e Pesquisa, 2010)
The theme of this text is the limits and possibilities of the philosophy teacher in the teaching-learning relation established in the classroom. Locating the fundamental elements of the pedagogical process - such as the teaching, the role of the teacher, the philosophical experience, and the pedagogical meaning of re-learning what has been learned -, the pedagogical context is reflected upon through its agents and through the objective in sight: the knowledge that allows the integration of knowledges. Drawing on the contribution of Hannah Arendt's thinking related to the clarification of one of the many issues in the crisis of education, which, according to the author is the collapse of the teacher's authority, the text recovers the fundamental role of the teacher in the teaching-learning game. Such recovery becomes possible when the teaching practice is rethought in the terms of its own grounding, and under its wider perspective: human formation. Along the text the pedagogical proposals of education thinkers as related to the teaching of philosophy to secondary education classes contribute to the understanding of the perspectives put forward in dealing with this issue. Elements such as learning, content, teaching and educational process are resumed in such a way as to help apprehending the truly philosophical meaning of the philosophy discipline. Crucial to this achievement is experience, which is not empirically characterized, but is conceived in the way its searches to contribute to the development of the form of understanding and developing the teaching of philosophy, and equally in its intention to allow the flourishing of new ways of learning as affording a truly philosophical experience.